Analisis Pengaruh Promosi dan Lokasi Terhadap Keputusan Menjadi Anggota Pada Gapoktan Mulya Jaya Unit LKMA Amanah Mandiri - Adhitya, Toni (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2023)
The purpose of this research is to find out how much influence promotion and location variables have on the decision to become a member of the Gapoktan Mulya Jaya Unit of LKMA